Role of Duodenogastroesophageal Reflux in the Pathogenesis of Esophageal Mucosal Injury and Gastroesophageal Reflux Symptoms - Xiao-rong Xu; Zhao-shen Li; Duo-wu Zou; Guo-ming Xu; Ping Ye; Zhen-xing Sun; Qing Wang; Yan-jun Zeng (Canadian Journal of Gastroenterology, 2006)
BACKGROUND AND AIM: Patients with gastroesophageal reflux disease (GERD) usually suffer from acid reflux and duo-denogastroesophageal reflux (DGER) simultaneously. The question of whether DGER has an important effect on the development of GERD remains controversial. The aim of the present study was to investigate the role of DGER in the pathogenesis of GERD and its value for the diagnosis of nonerosive reflux disease (NERD).